MODEL PENDEKATAN PROSES DALAM PEMBELAJARAN MENULIS (ECRIRE) WACANA NARATIF PADA MAHASISWA SEMESTER III JURUSAN PENDIDIKAN BAHASA DAN SASTRA ASING PROGRAM STUDI PENDIDIKAN BAHASA PRANCIS - Santoso, Wahyudi Joko; Widayanti, Diah Vitri (Lingua, 2009)
This research focused on the Proces-Approach Model in Narrative DiscourseWriting Learning. The four research questions: (1) how are the third semesterstudentsÃ¢â¬â¢ perception in Language and Litterature Foreign Departement,French Education Study Programme on Proces Approach Model in NarrativeDiscourse of Writing Learning before a treatment, (2) how and how manypercents their capability of Narrative Discourse Writing are before a treatment,(3) how and how many percents their capability of Narrative Discourse Writingare after a treatment, and (4) how are the third semestre studentsÃ¢â¬â¢ perceptionin Language and Litterature Foreign Departement, French Education StudyProgramme on Proces Approach Model in Narrative Discourse of WritingLearning after the treatment? The perception data was taken by questionnairewhich was done 2 x, before and after the treatment, whereas thestudentsÃ¢â¬â¢capability to write a narrative discourse was used by pretest andposttest. The findings show that firstly, the pretest result is various. ThestudentsÃ¢â¬â¢s kwnoledge of definition narrative discourse reach 80 %, of narrativediscourse organition 92 %, of the experience writing of narrative discourse76%, and of the writing step 72 %. Besides, the studentsÃ¢â¬â¢ unknown of lexicaland grammatical marquers reach 80 % and 88 %. Secondly, totally, if I comparethe first and the second test, the result shows that the students who got A, B,and D decrease, from 1 to 0 student (5,26%), from 8 to 7 students (5,26%), andfrom 3 to 1 student (10,53%). But the students who got C and D increase, from5 to 8 students (15,79%) and from 2 to 3 students (5,26%). Finally, thestudentsÃ¢â¬â¢ perception after the treatment indicate a various result. 80 %students are not satisfied of theirs narrative discourse writings, 60 % studentsstill has some difficulties, 80 % students are conscious of theirs weakness, and84 % students agreed about the researcherÃ¢â¬â¢s evaluation.Keywords: capability, writing, narrative discourse, proces approach writing model